How interpretation makes international law : on semantic change and normative twists - Venzke, Ingo. (Oxford : Oxford University Press, 2012)
An account of how the practice of interpretation makes international law, drawing specific attention to the increasing authority of international courts and institutions. It analyses the role that language plays in shaping international law and addresses the key issue of how it contributes to the evolution of international norms.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International law